Atuação do arquiteto na produção do espaço urbano autoconstruído pela população de baixa renda - Juliana de Faria Linhares (2018)
This dissertation proposes the discussion of the action of the architect in the urban space self-constructed by the low income population, dedicating, in principle, to investigate the possible ways to make this practice viable. From this line of research, there arose the need to also discuss the methods and languages to be used by professionals. For this debate, the empirical experience of technical assistance was proposed at Vila Acaba Mundo, in Belo Horizonte, Minas Gerais, and also the survey of projects that propose technical action for the low income population in Brazil. Confronted and articulated with these analyzes - empirical and referential -, the discussions about the different interests and motivations involved in the architect 's performance in self-constructed contexts could be expanded. They have generated other questions, including the discourse of precariousness given to the self-build houses by the poor population and the role of the architect. It is important to point out that it is not intended here to answer questions only, but also to generate fissures in the system of production and teaching of Architecture and Urbanism, inserting new questions, fomented by the real work context of the professionals. The objective of this analysis is, finally, the investigation, experimentation and creation of other possible realities for the urban space built by the low income population.